1998
DOI: 10.1017/s1357729800009061
|View full text |Cite
|
Sign up to set email alerts
|

Flushing of mink (Mustela vison): effects on energy metabolism and some blood metabolites

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1357729800009061How to cite this article: R. Fink and A.-H. Tauson (1998). Flushing of mink ( Mustela vison): effects on energy metabolism and some blood metabolites. AbstractEnergy metabolism during flushing of mink (Mustela vison) in relation to a control group was studied by means of combining pooled data from balance and respiration experiments carried out in 1993 (experiment I) and 1994 (experiment II) and some blood metabolites from experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Period effects were significant for thyroid hormones and IGF-1 and with insulin there was only a tendency for them; concentrations decreased during restriction and increased during refeeding. These results were in good agreement with [17,18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Period effects were significant for thyroid hormones and IGF-1 and with insulin there was only a tendency for them; concentrations decreased during restriction and increased during refeeding. These results were in good agreement with [17,18].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, limited data have indicated that flush feeding may result in a more synchronised LH release and in more distinct peaks [42], but here, sampling frequency was too limited to allow for an un-ambiguous description of the LH release pattern. Also metabolic traits such as plasma concentrations of insulin and thyroid hormones [17] as well as IGF-1 [18] have been shown to be affected by energy supply prior to the breeding season, but the response has not been related to reproductive endocrinology.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease and increase in animal live weights in the FLUSH group indicated that the food intake was less than required for maintenance during restriction, while the energy intake during the refeeding exceeded the requirement. These results were in agreement with calculations on substrate oxidation in animals exposed to a similar feeding regime [31] which showed a high level of fat oxidation during periods of restriction, whereas protein oxidation provided the major contribution to the total heat production when the food supply was ample, and with results by Fink and Tauson [17] showing negative values for retained energy [22] showing direct proportionality between insulin and level of food intake, and own previous results in mink [17]. [17], pig [16] and sheep [27] showing that [10], which probably was caused by the handling in connection with blood sampling (mink: B o rsting and Damgaard [ 10] and rat: Gdrtner et al [19]).…”
supporting
confidence: 91%
“…Previous studies with sheep [22] and mink [17] [34] and pigs [5]. Blood glucose is the primary energy substrate used at the cellular level, and reduced concentrations may influence body composition [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation